FUNGSI DAN METABOLISME PROTEIN DALAM TUBUH MANUSIA - Fivi Melva Diana (Faculty of Public Health, Andalas University, 2009)
Latin America and developing countries 15-30% of natural child less age nutrition 0 until 4 year in the year 2005. In Indonesia, Yogyakarta (15, 1%) and the highest of Gorontalo (46, 11%),In West Sumatra ugly nutrient that is (30, 4%). Padang 2,2% children under five with ugly nutrient. One of the district in Padang having number of children under five with status of nutrient highest good is district of Nanggalo. Malnutrtition happened because lack of energy and protein. In our body Protein have many function for baby and adult, protein as energy source after carbohidrat, for growing and metabolism in our body.Protein has been metabolism by pepsine in gaster.